Nutritional status and associated socioeconomic factors among low-income Saudi females - Alrougui, Khulud; Alshammari, Ghedeir M.; Alrwis, Khalid N.; Alabdulkarem, Kholoud B.; Yahya, Mohammed Abdo (Frontiers in Sustainable Food Systems, 2025)
IntroductionObesity is most common among people with low incomes in high-income countries, although being overweight affects all socioeconomic categories. This study evaluated the nutritional and health status and their associated variables in low-income Saudi females.MethodsA structured questionnaire was used to collect participants’ (153 women) sociodemographic profiles and other health data (hypertension, diabetes, thyroid, and anemia status). Nutrient intake, anthropometric indices, minimal dietary diversity scores (MDDS), and lipid profiles were also measured. Chi-squared and Student-t tests were used to detect significant variation among groups, and Spearman correlation was used to determine factors affecting the nutritional status of women.Results and discussionAs their sociodemographic profiles varied greatly, some participants’ nutrient intake was significantly lower (p ≤ 0.01) than their dietary recommended intake (DRI). However, the anthropometric indices differed significantly between the women with high and low MDDS (p ≤ 0.01). The rate of females with obesity outperformed the other groups regarding MDDS, followed by those who are overweight. Furthermore, a significant (p ≤ 0.001) variation in lipid profile was observed between subjects. Despite the majority of participants having normal cholesterol, LDL-C, and triglyceride levels, their HDL-C levels were either at high risk or borderline risk. The majority of the participants showed no signs of anemia, hypertension, diabetes, or thyroid issues. Interestingly, whereas education level was negatively and significantly at (p ≤ 0.05 or p ≤ 0.001) linked with some anthropometric indices, the factors age, family size, source of income, social welfare benefits, and marital status were positively and significantly associated with some of these variables. According to this study, low-income Saudi females face several challenges in adopting a nutritional and healthy lifestyle, as indicated by the parameters evaluated.